Cerberus and the U.S. auto industry - Stowell, David P., (SAGE Knowledge. Cases., 2017)
This case explores how and why GM became a major user of private equity and hedge fund capital, as well as the risks and rewards of these new relationships. The Cerberus transaction, audacious in both its size and complexity, is explored in detail. What were the alternatives for GM, and what risks and opportunities lay ahead for both parties? This case investigates the benefits, disadvantages, and potential conflicts of interest that evolved as GM's many suppliers increasingly embraced low-cost, nontraditional financing from hedge funds.